Lead dislodgement after a very long‐term period of cardiac implantable electronic device implantation. Issue 6 (15th September 2021) - Iwakawa, Hidehiro; Terata, Ken; Yamanaka, Takayuki; Tashiro, Haruwo; Watanabe, Hiroyuki
Abstract: A 74‐year‐old man was admitted for a second replacement of a transvenous implantable cardioverter‐defibrillator (ICD) generator at 15 years after implantation. Postoperatively, electrocardiographic monitoring showed atrial lead malfunction. Chest X‐ray revealed that the tip of the active fixation atrial lead was dislocated. We present a case of atrial lead dislodgement after a very long‐term period of an ICD implantation. Abstract : Lead dislodgement is the most frequent complication related to cardiac implantable electronic device (CIED) implantation, and if it occurs it is usually within few months after insertion. We present a case of atrial lead dislodgement 15 years after CIED implantation